Notes on the Cupressaceae in Vietnam - Rushforth, Keith (Academia Journal of Biology, 2014)
The taxonomy of the species of Cupressaceae indigenous to Vietnam is reviewed. Cupressus tonkinensis Silba is considered the correct name for the Cupressus in Langson province, not Cupressus torulosa. The genus Xanthocyparis is reduced to a subgenus of Cupressus and the new combination Cupressus vietnamensis (Farjon & Hiep) Rushforth made. The genus Fokienia is not considered separable from Chamaecyparis and the combination Chamaecyparis hodginsii (Dunn) Rushforth is made. The conifers associated with Cupressus vietnamensis and their conservation are discussed.